Narramos cuentos - Mendieta Cueva, Magnita (2018)
Through the development of this Learning Session, it is intended to develop in students their oral communication skills, assuming the role of narrator and listener, when telling stories. The development of active listening will be taken into account, learning to alternate in his role as a listener and speaker, assuming the characteristics that each of these roles implies, such as knowing how to express a high volume of voice, express yourself clearly, follow a sequence when narrating and learn to make appropriate use of body language and resources such as the images of the stories to be told. In turn, they will not only learn to express themselves orally, but also to understand oral messages that other people intend to communicate. To do this, it will start from the use of motivational reading: "The working chicken" hoping that the expected learning purposes will be achieved.